(untitled) (Journal of Asian Development Studies, 2024)
This research focuses on the widespread discrimination against transgender individuals within the healthcare industry resulting from a deeply rooted binary gender system. It seeks to gauge how much they are discriminated against, identify particular forms of discrimination by medical practitioners, and evaluate healthcare providers’ understanding gaps about transgender health needs. The investigation assumes that in healthcare facilities, transgender people receive substantial discrimination treatment; doctors carry out discriminatory actions as well as health facilitators or hospital administration know little about what is required for the wellbeing of such patients.The quantitative study involved 344 transgender individuals from 36 districts of Punjab. To find out the rates and types of discrimination as well as knowledge gaps among the data was subjected to chi-square tests, one-way ANOVA, and regression analysis. Results of chi-square tests revealed a significant relation between transgender identity and multiple discriminations such as postponements in treatment (χ² = 43.62, p < 0.001), denial of care (χ² = 67.21, p < 0.001), as well as financial discrimination (χ² = 138.23, p < 0.001). This research adds to existing knowledge about transgender health by showing how these individuals are discriminated against regularly and why educational as well as policy reforms in medical facilities should be implemented as a matter of urgency.